Detection of Aβ plaque-associated astrogliosis in Alzheimer's disease brain by spectroscopic imaging and immunohistochemistry. Issue 4 (12th December 2017) - Palombo, Francesca; Tamagnini, Francesco; Jeynes, J. Charles G.; Mattana, Sara; Swift, Imogen; Nallala, Jayakrupakar; Hancock, Jane; Brown, Jonathan T.; Randall, Andrew D.; Stone, Nick
Abstract : Correlative vibrational spectroscopy and immunohistochemistry reveal astroglial processes co-localised with the lipid-rich shell of Aβ plaques. Abstract : Recent work using micro-Fourier transform infrared (μFTIR) imaging has revealed that a lipid-rich layer surrounds many plaques in post-mortem Alzheimer's brain. However, the origin of this lipid layer is not known, nor is its role in the pathogenesis of Alzheimer's disease (AD). Here, we studied the biochemistry of plaques in situ using a model of AD. We combined FTIR, Raman and immunofluorescence images, showing that astrocyte processes co-localise with the lipid ring surrounding many plaques. We used μFTIR imaging to rapidly measure chemical signatures of plaques over large fields of view, and selected plaques for higher resolution analysis with Raman microscopy. Raman maps showed similar lipid rings and dense protein cores as in FTIR images, but also revealed cell bodies. We confirmed the presence of plaques using amylo-glo staining, and detected astrocytes using immunohistochemistry, revealing astrocyte co-localisation with lipid rings. This work is important because it correlates biochemical changes surrounding the plaque with the biological process of astrogliosis.